Construction and Calculation of Reinforced Concrete Overlap with A High Spatial Work Effect - Azizov, Taliat; Azizova, Anna; Al Ghadban, Sakr (International Journal of Engineering and Technology, 2018)
The article proposes the construction of a prefabricated monolithic reinforced concrete overlap consisting of beams hollow triangular section. It is shown that in such overlap the effect of spatial work is much higher than the analogous effect in traditional overlap that consists of U-shaped or T-beams and slabs. The technique of determining the forces of interaction of individual beams in the composition of the overlap is given. The technique is based on a discrete-continual method developed by the author, which is adapted to the calculation of overlaps that consist of considered beams. The technique of determining the effort between the shelf and the ribs of a beam during its bending is presented. It is based on the theory of compound rods. The algorithm of calculation taking into account the spatial work is presented as well as the principles of constructing overlaps consisting of beams hollow triangular section, taking into account the change in their rigidity as a result of cracks formation. An approach to the determination of the rigidity of beams with normal torsion fractures is given, based on the approximation of numerical experimental data.Â Â